Integração entre Estratégia Saúde da Família e vigilância em saúde: desafios para a prevenção e controle das arboviroses - Ana Paula de Figueiredo; Oldair Donizete Galeni; Eliene Aparecida da Cruz; Cleonice Alves da Cruz; Andréa de Ornelas Andrade Rodrigues; Divania Aparecida Santos Eugênio; Eliane June Maia; Adrielle de Cassia Fernandes; Meire Henriques Lopes Marcio; Vanessa Cristina Sassioto (Revista ft, 2026)
Arboviruses represent an important challenge for Brazilian public health due to their high transmission capacity, occurrence of epidemics, and relationship with environmental, social, and territorial factors. The prevention and control of these diseases require actions that go beyond individual care and incorporate epidemiological surveillance, vector control, health education, community mobilization, and intersectoral action. In this context, the integration between the Family Health Strategy and Health Surveillance represents a strategic element for the early identification of risks and the organization of interventions within the territory. This study aims to analyze the challenges and potential of integrating the Family Health Strategy and Health Surveillance for the prevention and control of arboviruses. This is a narrative literature review with a qualitative and descriptive approach, based on scientific studies and institutional documents related to Primary Health Care, Health Surveillance, and arboviruses. The findings indicate that territorialization, information sharing, integration between Community Health Agents and Endemic Disease Control Agents, health education, and joint planning can strengthen the response capacity of health services. However, fragmented work processes, communication difficulties, insufficient resources, and weaknesses in intersectoral coordination remain significant challenges. It is concluded that the integration between healthcare and surveillance is a fundamental strategy for strengthening continuous, territory-based, and participatory actions to address arboviruses.